Analysis of Cash Waqf Management in Indonesia and Malaysia: A Literature Highlight - Rafita, Dea Reren; Bella, Yeti Vera; Sugeng, Anggoro (Nuban Jagadhita Centre, 2023)
Purpose: Currently, the form of waqf is experiencing development, not only in the form of land waqf but also in the form of money or other financial objects. The waqf is known as cash waqf. Cash waqf is the latest breakthrough in the government's efforts to optimize the collection of waqf funds from its potential. In this study, researchers wanted to know about the management of cash waqf in 2 countries, namely Indonesia and Malaysia. Methodology: This research is descriptive qualitative, with data collection techniques in the form of Library Research. The data used is data obtained from the official websites of the Indonesian Waqf Agency (BWI) and the Malaysian Waqf Foundation (YWM). Findings: The results obtained from this study indicate that there are differences in waqf management in Indonesia and Malaysia. The difference lies in the method of waqf collection and distribution of waqf funds. In Indonesia, the collection of cash waqf is only divided into 2 forms, namely cash waqf and cash waqf, while in Malaysia the collection of cash waqf is adjusted to the purpose of its distribution. The collection of cash waqf in Indonesia tends to be spontaneous/unplanned and focuses more on developing productive waqf. Whereas in Malaysia the distribution of cash waqf tends to be patterned and regular, so that the form of distribution of funds tends to be the same from year to year, only the amount is different.